2011
DOI: 10.1162/jocn_a_00081
|View full text |Cite
|
Sign up to set email alerts
|

Neural Encoding of Objects Relevant for Navigation and Resting State Correlations with Navigational Ability

Abstract: Abstract■ Objects along a route can help us to successfully navigate through our surroundings. Previous neuroimaging research has shown that the parahippocampal gyrus (PHG) distinguishes between objects that were previously encountered at navigationally relevant locations (decision points) and irrelevant locations (nondecision points) during simple object recognition. This study aimed at unraveling how this neural marking of objects relevant for navigation is established during learning and postlearning rest. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
61
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(66 citation statements)
references
References 44 publications
3
61
2
Order By: Relevance
“…Santa Barbara Sense of Direction scale (SBSOD) Navigation ability was measured using the SBSOD scale (Hegarty et al 2002), which is a standard questionnaire on sense of direction in a large-scale environment, and is increasingly used as a reliable proxy for actual navigation ability (Janzen et al 2008;Wegman and Janzen 2011). SBSOD consists of 15 items.…”
Section: Behavioral Assessmentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Santa Barbara Sense of Direction scale (SBSOD) Navigation ability was measured using the SBSOD scale (Hegarty et al 2002), which is a standard questionnaire on sense of direction in a large-scale environment, and is increasingly used as a reliable proxy for actual navigation ability (Janzen et al 2008;Wegman and Janzen 2011). SBSOD consists of 15 items.…”
Section: Behavioral Assessmentsmentioning
confidence: 99%
“…Moreover, this scale has been increasingly used as a reliable proxy for real-world navigation performance in recent structural and functional neuroimaging literature (Janzen et al 2008;Wegman and Janzen 2011;Wegman et al 2014;Auger et al 2012;Epstein et al 2005). Therefore, SBSOD score, although based on participants' subjective experiences, is a valid index of the participants' real-world spatial navigation ability (see below for more discussion).…”
Section: Behavioral Assessmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, rsFC of task-relevant networks relates to individual differences in the consolidation of learned information, such that individuals with superior performance on a preceding learning task display the greatest changes in rsFC from a pre-to postlearning resting scan (e.g., Albert et al, 2009;Vahdat et al, 2011;Wegman and Janzen, 2011). In addition, the baseline (i.e., pretask) strength of rsFC in task-relevant networks can predict individual differences in subsequent performance, by which individual differences in the strength of selective resting-state networks relate to learning and memory ability (Baldassarre et al, 2012;Gordon et al, 2013;Wang et al, 2010aWang et al, , 2010bYstad et al, 2010).…”
mentioning
confidence: 99%
“…Several previous studies showed an increase in functional connectivity between hippocampal and extrahippocampal regions as a function of experience (Aly, Ranganath, & Yonelinas, 2013; Joost & Gabriele, 2011; Sulpizio, Boccia, Guariglia, & Galati, 2016), but there is evidence suggesting that training with lower intensity may lead to enhancement of previously established functional connections, while training with higher intensity may lead to increased efficiency (Karim et al., 2017; Penhune & Steele, 2012). Furthermore, a recent study focusing on the changes in functional connectivity and GABA levels with long‐term motor learning indicated that lower amounts of practice might rely mostly on the established connections by increasing the functional connectivity, whereas higher amounts of practice might cause formation of new connections and result in increased circuit efficiency reflected by decreased functional connectivity (Sampaiobaptista et al., 2015).…”
Section: Discussionmentioning
confidence: 99%